A diversified study on pesticide spraying equipment for vineyards using drones - Terenziano Raparelli; Gabriella Eula (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Some researcher groups in the Department of Mechanics and Aerospace Engineering (DIMEAS) Politecnico di Torino have an interesting experience with the applications of automatic systems in the agriculture fields [1-6].